2011
DOI: 10.1111/j.1747-1567.2011.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Soft-Rock Weathering Test Apparatus

Abstract: This paper presents a weathering test apparatus developed for testing the deformation and shear strength behavior of rockfill materials for high dams under coupling actions of drying/wetting cycles, cooling/heating cycles, and vertical loads. The apparatus was integrated with a vertical load unit, a lateral shear unit, a drying/wetting circulation unit, and a cooling/heating circulation unit. A cell was designed to perform direct shear tests under normal pressures up to 5.5 MPa after long‐term weathering assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Table 1 lists the test program. Testing procedures can be found in Zhang et al (2014). Five groups of tests were performed on the argillaceous siltstone under various conditions.…”
Section: Argillaceous Siltstonementioning
confidence: 99%
“…Table 1 lists the test program. Testing procedures can be found in Zhang et al (2014). Five groups of tests were performed on the argillaceous siltstone under various conditions.…”
Section: Argillaceous Siltstonementioning
confidence: 99%
“…So it is urgent to put forward the effective and simple support technique to determine the strain softening effect of weakly cemented soft rock. It has great difficulty of supporting the horse head in weakly cemented soft rock [5]. At the same time, and the cost of horse head engineering is much higher than the general tunnel because of its high importance and its long service life.…”
Section: Introductionmentioning
confidence: 99%
“…And in terms of unstable rock collapse source failure mechanism, research achievements are less open report. Qiang XU considered that there were key blocks on a steep cliff at the situation of outsize landslide from the cocktail mountain located in Wulong of Chongqing [2]; Yong-xing ZHANG analyzed the impact on the tensile stress in slope and the development depth of rock cavity to the formation and the destruction of differential weathering unstable rock [3]; Frayssines and Hantz analyzed failure mechanism of limestone on steep slope [4]; Hong-kai CHEN discussed damage characteristics [5] from dominant fissure top and fatigue crack characteristics under the action of crack hydraulic pressure based on damage and fracture mechanics [6], and proposed stability analysis method of unstable rock fracture [7]. In recent years, research has shown that unstable rock damage could abruptly release of energy, and the energy passed around in the form of excitation wave, which could affect the safety state of adjacent unstable rock.…”
Section: Introductionmentioning
confidence: 99%